Ethics and Finance : An Introduction - Hendry, John (Cambridge : Cambridge University Press, 2013)
Ethics and Finance: An Introduction provides a comprehensive and accessible introduction to the ethical issues raised by modern finance. Drawing carefully on ethical theory and with frequent use of case studies, it includes an analysis of the global financial system and its regulation and control, as well as a detailed analysis of the financial crisis. Chapters on specific areas of finance practice cover all the major financial scandals of recent times, from mis-selling to market manipulation and from insider trading to bankers' bonuses, as well as much more positive developments. From micro finance to derivatives trading, the book provides a careful and balanced treatment designed to help finance students and practitioners approach this sensitive topic in a thoughtful and constructive way. No prior knowledge of ethics or finance is required, and the book will be invaluable to students, finance teachers, practitioners and regulators.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Business ethics